A study on the current english language needs of the R&D departments in Kedah industrial sectors / Wan Irham Ishak…[etal.] - Ishak, Wan Irham; Md Salleh, Shafinah; Md Hashim, Azhari (Research Management Institude, 2005)
This research aimed to investigate the current English language needs in the R&D department of the Kedah industrial sector and to investigate the employers’ expectations of the employees in terms of their English language performance. This research utilized questionnaires to collect data from two groups of respondents namely the R&D department staffs and the administrators of the R&D department. 43 R&D department staffs and 10 administrators of the R&D department took part in this research. The results of the study revealed that English language is widely used by the R&D department staffs. The study also discovered that the R&D staffs are required to perform tasks such as presenting reports, dealing with clients, writing reports and interacting with superiors and colleagues in English. It was also discovered that the R&D staffs wished to improve their English language proficiency so that they could perform their job better. In addition, the administrators of the R&D department also felt that their subordinates should improve English language proficiency. The researchers have prioritized the skills that the R&D department staffs require. They are i) presentation skill in English language, ii) understanding and using technical terminology and vocabulary, iii) research and reading skills for design development purposes, and iv) interpersonal communication skills. In short, this research has identified the English language needs of the R&D department staffs and measures can be taken to equip the staffs with the necessary skills.